Kinetics of reactions of NH4 + with some biogenic organic molecules and monoterpenes in helium and nitrogen carrier gases: A potential reagent ion for selected ion flow tube mass spectrometry - Swift, Stefan James; Smith, David; Dryahina, Kseniya; Gnioua, Maroua Omezzine; Španěl, Patrik (Rapid communications in mass spectrometry, 2022)
RATIONALE: To assess the suitability of NH4 + as a reagent ion for trace gas analysis by selected ion flow tube mass spectrometry, SIFT-MS, its ion chemistry must be understood. Thus, rate coefficients and product ions for its reactions with typical biogenic molecules and monoterpenes need to be experimentally determined in both helium, He, and nitrogen, N2 , carrier gases. METHODS: NH4 + and H3 O+ were generated in a microwave gas discharge through an NH3 and H2 O vapour mixture and, after m/z selection, injected into He and N2 carrier gas. Using the conventional SIFT method, NH4 + reactions were then studied with M, the biogenic molecules acetone, 1-propanol, 2-butenal, trans-2-heptenal, heptanal, 2-heptanone, 2,3-heptanedione and 15 monoterpene isomers to obtain rate coefficients, k, and product ion branching ratios. Polarisabilities and dipole moments of the reactant molecules and the enthalpy changes in proton transfer reactions were calculated using density functional theory. RESULTS: The k values for the reactions of the biogenic molecules were invariably faster in N2 than in He but similar in both bath gases for the monoterpenes. Adducts NH4 + M were the dominant product ions in He and N2 for the biogenic molecules, whereas both MH+ and NH4 + M product ions were observed in the monoterpene reactions; the monoterpene ratio correlating (R2 = 0.7) with the proton affinity, PA, of the monoterpene molecule as calculated. The data indicate that this adduct ion formation is the result of bimolecular rather than termolecular association. CONCLUSIONS: NH4 + can be a useful reagent ion for SIFT-MS analyses of molecules with PA(M) < PA(NH3 ) when the dominant single product ion is the adduct NH4 + M. For molecules with PA(M) > PA(NH3 ), such as monoterpenes, both MH+ and NH4 + M ions are likely products, which must be determined along with k by experiment.
Keywords: dusík; Indicators and Reagents; Protons; Helium; indikátory a reagencie; helium; kinetika; hmotnostní spektrometrie; ionty; Ions; monoterpeny; Mass Spectrometry; Kinetics; Monoterpenes; Nitrogen; protony